THE INFLUENCE OF MOTIVATION, COMMUNICATION, AND ORGANIZATIONAL COMMITMENT ON PT. INTRACO PENTA WAHANA PALEMBANG EMPLOYEES' PERFORMANCE - Hernando Hendrik; Letifa Shintawaty; Liliana (Jurnal Kompetitif, 2023)
The purpose of this study is to find out: 1) to determine the effect of Motivation, Communication and Organizational Commitment on Performance simultaneously on Employee Performance at PT. Intraco Penta Wahana Palembang, 2) to determine the effect of partial motivation on employee performance at PT. Intraco Penta Wahana Palembang, 3) to determine the effect of partial communication on employee performance at PT. Intraco Penta Wahana Palembang. The sample in this study was employees of PT. Intraco Penta Wahana Palembang as many as 25 people from a total population of 25 people. The sampling technique uses saturated sampling. Data collection used questionnaires, validity tests and reliability tests, while data analysis was carried out using multiple regression analysis. The results of this study show that: 1) work effectiveness and loyalty simultaneously have a significant effect on employee performance at PT. Intraco Penta Wahana Palembang. It can be seen that the values of Fcalculate (7.598) > Ftable (3.42) with significance 0.003 < 0.05; 2) partial effectiveness has a significant effect on employee performance at PT. Intraco Penta Wahana Palembang. It can be seen that the calculated value of 2.095 > the ttable value of 1.71.  Significance test results of 0.003 < 0.05; and 3) partial loyalty has a significant effect on employee performance at PT. Intraco Penta Wahana Palembang. It can be seen that the calculated value of 2.404 > the ttable value of 1.71. Significance test results 0.001 < 0.05.